Impact of Adverse Childhood Experiences (ACE) and Childhood Protective Factors (CPF) on physical and mental health of medical students of a public sector medical university. - Usman Ali; Nazish Imran; Muhammad Shaheryar Khan (PLOS Global Public Health)
The current study aimed to assess the impact of Adverse Childhood Experiences (ACE) and Childhood Protective Factors (CPF) on physical and mental health of medical students of a public sector medical university. An online cross-sectional descriptive study was carried out at a public sector medical university in Lahore, Pakistan from 1 June 2024 to 30 August 2024. The study tool consisted of sociodemographic questions, an Adverse Childhood Experience (ACE) questionnaire, and a Resilience Questionnaire for measuring childhood protective factors and self-reported physical and mental health in the last 4 weeks. Data was entered and analyzed using Statistical Package for Social Sciences (SPSS) Version 26.0. A total of 368 medical students participated in the survey of which 125 (33.96%) were male and 243 (66.03%) were females. A higher Childhood Protective Factor (CPF) score significantly predicted good physical health (AOR 1.516, 95% CI 1.085-2.120, p <.01) and excellent physical health (AOR 1.61, 95% CI 1.151-2.263, p <.001). A higher ACE score significantly predicted fair mental health (AOR .767, 95% CI .624-.944, p <.05), good mental health (AOR .746, 95% CI .604-.922, p <.01), and excellent mental health (AOR .746, 95% CI .604-.922, p <.01). Our study shows that ACE was a significant predictor of self-reported mental health but not physical health. However, CPF was a significant predictor of physical and mental health.